THE DIVERSITY OF PHYTOPHAGE AND ENTOMOPHAGE INSECT SPECIES IN SUGARCANE PLANTATIONS PLANTED WITH FLOWERING PLANTS - Azim, Saida Fitriani; Irsan, Chandra; Pujiastuti, Yulia (BIOVALENTIA: Biological Research Journal, 2020)
This study aimed to know the influence of planting the flowering plants in sugarcane plantation on the index value of diversity, domination, and the eveness of phytophage and entomophage insect species in sugarcane plantation. This study was done on two-month and six-month sugarcane of PT.Â  Perkebunan Nusantara VII Cinta Manis District. The research location is located in Ketiau Village, Lubuk Keliat District, Ogan Ilir Regency, South Sumatra. The study was conducted from July to December 2018. Insects that came to flowering plants were collected by using fitfall traps, nets, and direct capture of insects that came. The results showed that the age of sugarcane affected the diversity of Entomophage and Phytophage insect species that came to the flowering plants. At 2-moth-old sugar cane plantations were found 42 species (388 individuals) and 6-month-old sugarcane plantations were found 41 species (284 individuals). The diversity of Phytophage and Entomophage species that came to flowering plants inÂ  the 2-month-old sugarcane plantations was almost the same as in the 6-month-old sugarcane plantations. Phytopage species diversity index values were 2,826 and 2,548, while Entomophage were 2,564 and 2,867.